1998
DOI: 10.1161/01.cir.97.24.2396
|View full text |Cite
|
Sign up to set email alerts
|

Interlesion Dependence of the Risk for Restenosis in Patients With Coronary Stent Placement in Multiple Lesions

Abstract: Background-Little is known about the behavior with regard to restenosis of multiple lesions within the same patient treated with intracoronary stenting. Our objective was to test the hypothesis that there is an intrapatient dependence of restenosis between lesions. Methods and Results-Quantitative analysis was carried out on angiograms obtained before, immediately after, and at 6 months after coronary stent placement in 1734 lesions in 1244 patients. We used a specialized logistic regression that not only acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 43 publications
(36 reference statements)
2
34
0
3
Order By: Relevance
“…The distribution of late loss for the Cypher stent appeared largely skewed to the right with a Gaussian distribution. 29) In addition, we found that late loss was higher in the Taxus stent group than in the Cypher stent group, demonstrating that late lumen loss tended to favor the Cypher (Fig. 2).…”
Section: Patient-related Factorsmentioning
confidence: 70%
“…The distribution of late loss for the Cypher stent appeared largely skewed to the right with a Gaussian distribution. 29) In addition, we found that late loss was higher in the Taxus stent group than in the Cypher stent group, demonstrating that late lumen loss tended to favor the Cypher (Fig. 2).…”
Section: Patient-related Factorsmentioning
confidence: 70%
“…In patients with multivessel disease, the incidence of restenosis of a second lesion was 2.5 times higher if the first lesion had restenosis, even after adjustments for well-known patient-related risk factors, including diabetes and hypertension. 9 Inflammatory responsiveness is highly genetically determined. Many studies have demonstrated genetic influences on the inflammatory response of an individual.…”
Section: Editorial P 2378mentioning
confidence: 99%
“…4,5 Several lines of evidence indicate that genetic factors may explain the excessive risk of restenosis independently of conventional clinical and procedural parameters. 6,7 Consequently, additional genetic tests to identify patients at increased risk of restenosis may lead to improved risk stratification and eventually individual, patient-tailored therapy. This concept has resulted in genetic studies designed to identify single nucleotide polymorphisms (SNPs) in genes associated with restenosis.…”
mentioning
confidence: 99%